LITERATURE REVIEW: IMPACT OF THE COVID-19 PANDEMIC ON THE TEACHING AND LEARNING PROCESS - Saputro, Bambang Eko; Nunung Julaeha (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The COVID-19 pandemic has created the largest disruption to education systems in human history, affecting nearly 1.6 billion students in more than 200 countries. The closure of schools, institutions and other learning spaces has affected more than 94% of the world's student population. It has brought about vast changes in all aspects of our lives. Social distancing policies and movement restrictions have significantly disrupted traditional educational practices. The reopening of schools after the easing of restrictions is another challenge with many new standard operating procedures being put in place. In the short span of time from the COVID-19 pandemic, many researchers have shared their work on teaching and learning in different ways. Some schools, colleges and universities have stopped face-to-face teaching. There is a fear of missing out on the 2020 school year or even more in the future. The need now is to innovate and implement alternative education systems and assessment strategies. The COVID-19 pandemic has given us the opportunity to pave the way for introducing digital learning. This article aims to provide a comprehensive report on the impact of the COVID-19 pandemic on online learning of various papers and show the way forward.